typo/graphic days 6 - Panayides, Angelos (My University, 2023)
The poster was selected in the category B. Art of the Spectacle Posters For the purpose of this thematic we understand Spectacle as an Act. A theatrical, music, artistic or any other performance is seen as a culturally driven act. Under this category we welcome posters negotiating cultural action or activities as spectacle.
Keywords: Trienale; Poster; Graphic Design